2021
DOI: 10.1161/strokeaha.120.033676
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital Triage Accuracy in Patients With Stroke Symptoms Assessed Within 6 to 24 Hours or With an Unknown Time of Onset

Abstract: Background and Purpose: The Stockholm Stroke Triage System, implemented in 2017, identifies patients with high likelihood of large vessel occlusion (LVO) stroke. A previous report has shown Stockholm Stroke Triage System notably reduced time to endovascular thrombectomy (EVT). As the indication for EVT now includes patients up to 24 hours, we aimed to assess Stockholm Stroke Triage System triage accuracy for LVO stroke and EVT treatment for patients presenting late (within 6-24 hours or with an unk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…This system combines prehospital assessment of hemiparesis with ambulance-to-hospital teleconsultation, to triage cases with high likelihood of EVT-eligible LAO to CSC. 15,16 During the first year after implementation, onset to puncture time for EVT was reduced from 206 to 137 minutes. The triage system's accuracy for LAO stroke was 87% and for treatment with EVT, 91%.…”
mentioning
confidence: 99%
“…This system combines prehospital assessment of hemiparesis with ambulance-to-hospital teleconsultation, to triage cases with high likelihood of EVT-eligible LAO to CSC. 15,16 During the first year after implementation, onset to puncture time for EVT was reduced from 206 to 137 minutes. The triage system's accuracy for LAO stroke was 87% and for treatment with EVT, 91%.…”
mentioning
confidence: 99%
“…It is important to note that a review of currently existing triage scales for ELVO supported that different scales may have a different sensitivity and/or specificity in different settings (field, emergency department) [ 20 ]. The Stockholm Stroke Triage System (SSTS), which includes a physical exam for hemiparesis, real-time screen by a nurse, and a telehealth assessment by a stroke expert, achieved 95% specificity in both detecting ELVO and the need for MT [ 21 ]. In addition, specificity and overall accuracy were statistically significantly higher in the patient group that presented within 6 h after symptoms onset [ 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…The Stockholm Stroke Triage System (SSTS), which includes a physical exam for hemiparesis, real-time screen by a nurse, and a telehealth assessment by a stroke expert, achieved 95% specificity in both detecting ELVO and the need for MT [ 21 ]. In addition, specificity and overall accuracy were statistically significantly higher in the patient group that presented within 6 h after symptoms onset [ 21 ]. In a case-control study, triaging stroke patients with SSTS in the field resulted in faster MT times without delaying IV thrombolysis [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The SSTS combines a test for moderate-to-severe hemiparesis with ambulance-hospital teleconsultation, to identify patients with a high likelihood of LAO with EVT indication, for PSC bypass. The SSTS predicts LAO and EVT with high accuracy both within 6 and 6-24 h from onset or last known well, and has reduced regional median onset-to-puncture time in EVT by 69 min, without delaying IVT (2,3). Studies on AIS have found that, unlike greater mortality, the lower poststroke functional level and quality of life in women remains significant after adjustment for prestroke mRS and age (4-6).…”
Section: Introductionmentioning
confidence: 99%